Exploring the role of immune checkpoint inhibitors in the etiology of myasthenia gravis and Lambert-Eaton myasthenic syndrome: A systematic review - Seligman, Carly; Chang, Yu-Mei; Luo, Jie; Garden, Oliver A. (Frontiers in Neurology, 2023)
Background: While immune checkpoint inhibitors (ICIs) have been revolutionary in the treatment of cancer, their administration has been associated with a variety of immune-related adverse events (irAEs), including myasthenia gravis (MG) and Lambert-Eaton myasthenic syndrome (LEMS). Objective: To provide a comprehensive synthesis of the evidence supporting an etiological role for ICIs in MG and LEMS in patients with no prior history of autoimmune disease. Hypothesis: ICIs may trigger MG and LEMS in patients with no prior susceptibility to autoimmune disease. Methods: Relevant primary research on Medline was interrogated using a series of search algorithms. Search terms were constructed based on the PICOS tool endorsed by the Cochrane Collaboration, which describes population, intervention, comparison, outcomes, and study design. Papers were screened according to inclusion and exclusion criteria. Additional papers were retrieved from the reference lists of screened papers. Each paper included in the qualitative synthesis was assigned an integrated metric of evidence (IME) value, ranging from 0 to 7, based on study design, quality of data, likelihood of a causal link between the immune checkpoint inhibitor(s) and MG/LEMS, confidence of MG/LEMS diagnosis, and the number of patients treated with an ICI prior to MG/LEMS diagnosis. Results: Ninety-four papers describing at least one patient treated with ICI(s) prior to the onset of MG and/or LEMS were documented. Overall evidence for a causal link between ICI administration and MG/LEMS was low, with a median IME value of 2.88 (range 2.05 to 6.61). Conclusions: There is a paucity of evidence in support of an etiological relationship between ICIs and MG/LEMS, due largely to the lack of mechanistic studies and/or prospective clinical trials with relevant study endpoints. The current literature is dominated by case reports and retrospective cohort studies, which inherently yield only low-level evidence, supporting the need for further work in this area. A role of ICIs in the etiology of MG/LEMS remains plausible, arguing for continued vigilance for irAEs in patients treated with these drugs. We argue that there is a need for future mechanistic, high quality, large-scale studies specifically investigating the possible etiological role of ICIs in MG/LEMS.